2012
DOI: 10.1007/s11481-012-9374-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prenatal Immune System Disturbances on Brain Development

Abstract: As research into various aging-associated neurodegenerative disorders reveals their immense pathophysiological complexity, the focus is currently shifting from studying changes in an advanced disease state to investigations involving pre-symptomatic periods, possible aberrations in early life, and even abnormalities in brain development. Recent studies on the etiology of schizophrenia and autism spectrum disorders revealed a profound impact of neurodevelopmental disturbances on disease predisposition, onset an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Beyond their role as the "conventional macrophages of the brain," microglia have fundamental roles in synaptogenesis (Kettenmann, Hanisch et al 2011). As we discuss in detail in the next section, aberrant glial-neuronal interactions are important players in early stages of AD and other adult neurodegenerative diseases (Madhusudan, Vogel et al 2013, Bilbo and Stevens 2017.…”
Section: Microglial Plasticity Due To Fetal and Neonatal Insults: A Mmentioning
confidence: 99%
“…Beyond their role as the "conventional macrophages of the brain," microglia have fundamental roles in synaptogenesis (Kettenmann, Hanisch et al 2011). As we discuss in detail in the next section, aberrant glial-neuronal interactions are important players in early stages of AD and other adult neurodegenerative diseases (Madhusudan, Vogel et al 2013, Bilbo and Stevens 2017.…”
Section: Microglial Plasticity Due To Fetal and Neonatal Insults: A Mmentioning
confidence: 99%
“…Microglia are a heterogeneous family of cells of myeloid lineage, which migrate from the bone marrow to the CNS both pre- and postnatally, and play a currently underappreciated role in neurodevelopmental disorders (165). When activated, they produce high levels of proinflammatory cytokines and reactive oxygen species such as hydrogen peroxide and nitric oxide.…”
Section: Neuropathological Effects Of Ppa Infusions On Inflammation/cmentioning
confidence: 99%
“…Numerous theories have been proposed regarding the cause of schizophrenia. Recent studies on pathophysiology of schizophrenia revealed impact of immunological and inflammatory mechanisms on disease predisposition, onset and progression (2). The neuropathological studies found associations between schizophrenia and both abnormal levels of inflammatory cytokines, and increased frequency of activated lymphocytes (3).…”
Section: Introductionmentioning
confidence: 99%